ISLAMIC VALUE OF INNOVATIVE PERFORMANCE IN SMALL AND MEDIUM-SIZED ENTERPRISES: CONCEPTUAL REVIEW OF FATHANAH - Nur Rahmah; M. Wahyuddin Abdullah; Salmah Said (Jurnal Iqtisaduna, 2019)
Small and medium-sized enterprises (SMEs) contribute to the national economy. It follows to increase in market potential. Innovation has an important role in various business competitions. However, innovative performance has not been completely implemented by SME companies. This research offers the concept of fathanah in innovative performance in SMEs. The research method is a review of the literature on SME innovative performance. This study explains the innovative performance of SMEs with six concepts; process innovation, product innovation, management innovation, organizational innovation, marketing innovation, and technological innovation. The concept of fathanah in innovative performance in SMEs with dimensions of intelligence; intellectual quotient (IQ), emotional quotient (EQ), and spiritual quotient (SQ). This paper applies a conceptual approach. The limitations of this paper are that the dimensions mentioned have not been empirically tested. In addition, there may also be other dimensions of Islamic values related to innovative performance apart from the concept of fathanah. However, the fathanah concept is expected to be applied in innovative performance to develop SMEs.